Simulation of Sintering across Scales. Issue 7 (29th April 2019) - Raether, Friedrich; Seifert, Gerhard; Ziebold, Heiko
Abstract: Sintering controls microstructure and quality of powder‐metallurgical and ceramic products and the efficiency of heating processes. A survey on computational tools for the simulation and optimization of sintering processes is presented including both microstructural models and continuum mechanical models. A new integrated microstructure model on sintering (IMS) is introduced. It includes the most important aspects of current computational microstructural models on solid state sintering: local equilibrium structures controlled by interface energy, randomness of diffusion processes, and particle rearrangement. The model assumptions and the underlying equations are described in detail. Simulations based on the IMS model show a very realistic evolution of microstructure. They require reasonable computer time and show small statistical variations. Various applications of the new model are suggested and its limitations are discussed. For the prediction of shrinkage and shape distortions during sintering, continuum models are required which are based on input from sintering experiments. Adequate functions of the different models and criteria for their efficient interplay with measurements are proposed according to an integrated computational materials engineering approach for sintering. Abstract : Various approaches for the simulation of sintering processes on the micro‐ and macroscale have been established, often driven by technological requirements for process optimization. Here, a survey of the most important concepts and their achievements is given. Recent progress in developing an integrated microstructural simulation of sintering and in predictive macroscopic modeling of real component sintering is discussed.